Analisis Penerapan Sistem Informasi Kesehatan Daerah (SIKDA) Generik Dalam Meningkatkan Pelayanan Rawat Jalan Di Puskesmas Rawat Inap Ciranjang - Muhammad Naufal Fernanda; Ade Irma Suryani (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
The use of good information system technology can help the implementation of the work program of the puskesmas effectively, reports on the performance of the puskesmas can be reported periodically and systematically so that the puskesmas management can make the right decisions. SIKDA at the Medical Record Unit at the Ciranjang Inpatient Health Center just started in April 2019. This study aims to analyze the implementation of the Regional Health Information System (SIKDA) in improving outpatient services at the Ciranjang Inpatient Health Center and to analyze the inhibiting factors for the implementation of generic SIKDA at the Ciranjang Inpatient Health Center. The research method used is qualitative analysis with a descriptive approach. The time of the research was conducted in March-May 2023 at the Ciranjang Inpatient Health Center. The results of the study when viewed from the perspective of human factors found that SIKDA at the Ciranjang Inpatient Health Center could not be carried out by every officer in the service unit, there were no special technical staff who managed the information system and there was no further training or outreach. While from the technological factor there are several damaged devices and information systems that are not updated. It can be concluded that generic SIKDA human resources are still lacking in operating generic SIKDA in all outpatient service units due to limited human resources. The technological factor for the application of SIKDA is already very good. However, support from the leadership for the implementation of generic SIKDA is considered to be lacking due to limited facilities and infrastructure, and the availability of human resources. And the benefits generated by the regional health information system (SIKDA) at the Ciranjang Inpatient Health Center are still not being felt due to not being integrated in all outpatient services and software applications that have never been updated again.